Britain, America and extradition: Trial of an alien. (Economist, 2009)
There is unease in Great Britain over the impending extradition of a British subject to the U.S. on computer hacking charges. According to U.S. prosecutors, between 2001 and 2002, Gary McKinnon accessed 97 American military and NASA computers, allegedly causing $700,000 worth of damage. Extradition proceedings against McKinnon have caused an outcry in Britain, partly because the current extradition arrangements between the two countries are viewed as lopsided. Whereas Britain must demonstrate “probable cause” before a suspect can be extradited from the U.S., its prosecutors need only prove “reasonable suspicion” before Britain extradites a suspect. According to McKinnon's supporters, if he has to stand trial, then he should do so in Britain because of a diagnosis of Asperger's syndrome, which would not be considered in a U.S. trial, and his possible imprisonment.